Marker-trait association for fertility restoration using Rf8 gene in T. timopheevii based male sterile cytoplasm of wheat - Bakala, Harmeet Singh; Srivastava, Puja; Vinod, Vinod; Ankita, Ankita; Sharma, Achla; Mavi, Gurvinder Singh (Journal of Cereal Research, 2020)
Hybrid wheat research has garnered interest after a gap of few decades. Heterosis levels and effective ABR system has been continuous focus of research. Effective restoration of fertility, its genetic control however remains an unresolved issue. Among 9 reported fertility restorer genes for Triticum timopheevii cytoplasm, Rf8 has been mapped on chromosome 2DS. Two F2 populations were used to study the efficacy and robustness of markers linked with Rf8. Data was recorded on extent of fertility restoration and three linked markers namely Xwmc503, Xwmc296 and Xwmc112 were used for this study. Among these, Xwmc503 present at 3.3 cM away from Rf8 showed significant association with fertility restoration in both the crosses. In contrast, marker Xwmc296 linked at 5.8 cM did not reveal significant association in any population. However, the third marker Xwmc112 did not get amplified in any of the populations. Xwmc503 marker can potentially be useful for selecting restorers with Rf8 gene which further could be used for transferring this very gene into potentially elite genotypes to enrich hybrid male parental pool.